L’Étrange cas de Coleman Silk, le Jewbird de The Human Stain de Philip Roth - Frédéric Dumas (Revue LISA)
Coleman Silk was born white in a black family. His decision to take his destiny into his own hands brought about his social success but also his disconnection from his family, his transformation into an eternal stranger and his eventual fall as the scapegoat of his New England campus. He is a true tragic hero in a crypto-mythical environment and has a lot in common with Malamud’s Jewbird, which seems to have made its way into a cage at the local Audubon Society. This mysterious presence raises the question of the essentially fictional nature of Coleman Silk’s edifying story within the diegesis, for the narrator’s imagination makes up a paradoxical pattern combining both estrangement and revelation.